Embedding Trust Factor into ICT-Based Knowledge Sharing Framework for Cassava Farmers in the Informal Organization - Ukpe, Emmanuel Friday Ogunbor (2023)
The progression of Information and Communication Technology (ICT) has enabled organizations to share knowledge and collaborate from diverse locations with experts; to accomplish organizational tasks. However, the characteristics and dynamics of informal organizations have posed various challenges to good knowledge sharing, especially in a virtual environment. The literature on organizational knowledge sharing has shown that the investigations on different constructs of organizational knowledge sharing indicate that trust has been one of the essential aspects to be addressed. Informal organization, particularly in a virtual environment, may pose additional challenges when the knowledge owner and knowledge seeker do not know each other. Establishing the trust model and embedded into the theoretical framework in a web-based knowledge-sharing platform is demonstrated in this research. A virtual knowledge-sharing environment is facilitated using a web-based portal and mobile devices, so-called Knowledge Acquisition Processing, and Exchange (KAPE). Trust-Based Knowledge Sharing Framework (TBKSF) is established based on the notion to be applied in the informal setting of an organization using KAPE, which encompasses (a) A web-based knowledge of the entire Cassava plantation, (b) Cassava Yield Simulation, (c) Downloadable Cassava production video, and (d) Mobile Application. A survey was conducted, and data were collected from 382 farmers (Cassava and mixed crop farmers) drawn from 7 states, 21 farm communities, and interviewees. Observations were made over three years and nine months. To test the hypothesis and determine meaningful relationships, Cronbach’s Alpha, a reliability test; Tukey’s Honestly significant difference (HSD) analysis; PLS-SEM, Pearson Product Moment Correlation (PPMC), and all trust acceptable measures (TAM) were used to test the hypothesis. The findings revealed that identifying and managing factors that enable trust in knowledge sharing would positively facilitate knowledge sharing in the informal setting (β = 0.412, t-value = 2.955). However, there was no significant association between satisfactory factors that validated the knowledge source and acceptance of the knowledge provided (β = -0. 062, t-value = 0.518). Equally, a trust model (integrating all acceptable trust measures) can be built on a computational knowledge-sharing platform for informal organizations where workers are unfamiliar with each other (β = 0.436, t-value = 4.258). Hence, positively, a trust model (integrating all acceptable trust measures (TAM) can be built on knowledge sharing for the informal organization in an informal setting for workers who are not familiar with each other. Furthermore, there was a significant relationship between KAPE, a knowledge-sharing platform, and an increase in Cassava production (r=0.784, p<0.000). Similarly, there was a significant positive result in farming activities and yield, the using KAPE trust model in knowledge sharing in the rural community of practice amongst cassava growers (r=0.703, p<0.000) showed a positive relationship between the variables, and the relationship was statistically significant at 1%. The result implies that the adopted trust model (KAPE) positively improves knowledge-sharing activities amongst rural farmers based on trust. Notably, the research findings revealed that trust and the farmers shared cultural values have a beneficial impact on sharing knowledge. Finally, the result shows that the success of any virtual team must be built on trust because it was the strength of trust relationship amongst the farmers that provides the underpinning for their willingness to share and knowledge-sharing effectiveness in these informal agricultural communities.